In vino veritas: Theory and evidence on social drinking - Justus Haucap; Annika Herr; Björn Frank (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2011)
It is a persistent phenomenon in many societies that a large proportion of alcohol consumption takes place in company of other people. While the phenomenon of social or public drinking is well discussed in disciplines as social psychology and anthropology, economists have paid little attention to the social environment of alcohol consumption. This paper tries to close this gap and explains social drinking as a trust facilitating device. Since alcohol consumption tends to make some people (unwillingly) tell the truth, social drinking can eventually serve as a signaling device in social contact games. Empirical support is obtained from a cross-country analysis of trust and a newly developed index of moderate alcohol consumption.
Keywords: C72; D71; L14; 330; social and public drinking; alcohol consumption; social contact games; trust; signaling